The Relation Between Students’ English Language Proficiency and Their Academic Performance: An Empirical Analysis - Renganathan, Sumathi (2008)
This paper empirically examines the relationship between English language proficiency and students’ academic performance. Studies have indicated that students’ proficiency in English contributes to their academic success. In this study however, we focus on students from schools where English is not the main language, but who have decided to further their studies in an institution which uses English as its medium of instruction. Thus, this study investigates how these students themselves perceive the role of English language for their academic success.